ASSOCIATION OF GENOTYPES OF POLYMORPHISMS OF GENES FGFR2, LSP, AND LOC643714 WITH THE RISK OF A POSITIVE MUTATIONAL STATUS OF THE HER-2/NEU GENE IN BREAST CANCER PATIENTS - Bogdana Klimuk; Svitlana Polinik; Lyudmila Ribchenko; Lubov Zakhartseva; Oleksyi Dugan; Sergiy Klymenko (Bogomolets National Medical University, 2020)
Breast cancer is the result of genetic and environmental factors that lead to the accumulation of mutations in key regulatory genes. Genetic predisposition to cancer pathologies may be due to mutations in individual genes, such as in BRCA1 and BRCA2, or may be due to a cumulative effect as a result of the interaction of genes of low penetrance. This paper reviews the alleles that determine the risk of high and low penetrance breast cancer and discusses ongoing efforts to identify additional susceptibility genes. The identification of propensity genes is a prerequisite for an individualized assessment of breast cancer risk and a decrease in the incidence of breast cancer. The main goal of this study is to determine the associations of polymorphic variants rs2981582 and rs1219648 of FGFR2, rs3817198 of LSP and rs3803662 of LOC643714 with the risk of breast cancer and the development of a positive mutational status of Her-2/neu. The study group included 300 women diagnosed with breast cancer. Fluorescent in situ hybridization was performed on tumor tissue materials from these patients to determine the amplification status of the Her-2/neu. The distribution of genotypes and alleles was performed by real-time polymerase chain reaction for the following polymorphic variants rs1219648 of FGFR2 (n = 44), rs2981582 of FGFR (n = 99), rs3817198 of LSP1 (n = 75) and rs3803662 of the LOC643714 (n = 82). Among the studied genotypes of polymorphic variants rs3817198 of LSP1, rs3803662 of LOC643714, rs2981582 and rs1219648 of FGFR2, with the inclusion of the risk allele, the association of the propensity to develop breast cancer in women according to the multiplicative model of inheritance (p> 0.05) was not determined. According to the codominant inheritance model, there is an associative relationship with the risk of breast cancer and polymorphism rs3817198 of LSP1, rs3803662 of LOC64371 and rs2981582 of FGFR2 with homozygous genotypes for rare alleles (p <0.05). Women with a positive amplification status of the Her-2/neu, patients with breast cancer, were more likely to carry the risk allele G (OR = 4.80; 95% CI 1.21-28.04, p <0.05) and genotype GG ( OR = 5.82; 95% CI 1.38-16.74, p <0.05) rs3803662 polymorphism of LOC643714, compared with a group of women with negative amplification status of Her-2/neu in patients diagnosed with breast cancer. The results of this study can be useful for searching for additional genetic predictors of breast cancer and a positive mutational status of Her-2/neu.